MANAJEMEN PENINGKATKAN MUTU SEKOLAH DASAR NEGERI TUNTANG 03 KECAMATAN TUNTANG KABUPATEN SEMARANG - Dewi Setianingsih; Ngasbun Egar; Ghufron Abdullah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study was to analyze and describe (1) school quality planning at SD Negeri Tuntang 03 Semarang Regency, (2) school quality organization at SD Negeri Tuntang 03 Semarang Regency, (3) school quality implementation at SD Negeri Tuntang 03 Semarang Regency and (4) school quality supervision at SD Negeri Tuntang 03 Semarang Regency. This study uses a qualitative descriptive method with a case study research type, the subjects of this study are the principal, teachers, School Quality Assurance Team and school committee. Data collection techniques are interviews, documentation and observation. Data analysis used is qualitative analysis including data collection, data reduction, data display and drawing conclusions. The results of the study indicate that (1) The school quality planning process at SDN Tuntang 03, Semarang Regency is quite good where the school has a quality policy, availability and readiness of GTK, and has high achievement expectations. (2) The organization of school quality is carried out well, the formation of TPMS and the Internal Audit Team at the organizational stage is carried out based on good selection. (3) The implementation of school quality is quite good by running priority scale programs: implementing differentiated learning and holding excellent school programs, (4) Supervision of school quality is quite good, namely by internal and external audit teams.